Traditional Chinese Medicine in the Management of Anxiety Disorders: A Narrative Review of Theoretical Foundations, Clinical Applications, and Modern Integrative Approaches - Wang Q; Wang D; Lv Y; Li Q (Neuropsychiatric Disease and Treatment)
Qi Wang,1 Delong Wang,2 Yuying Lv,3 Quan Li1 1Basic Theory of Traditional Chinese Medicine, College of Basic Medicine, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150006, People’s Republic of China; 2Laboratory of Neurobiology (Encephalopathy) of Clinical Acupuncture, The Second Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150001, People’s Republic of China; 3Internal Medicine-Cardiovascular Department, Harbin Hospital of Traditional Chinese Medicine, Harbin, Heilongjiang, 150699, People’s Republic of ChinaCorrespondence: Quan Li, Internal Medicine-Cardiovascular Department, Harbin Hospital of Traditional Chinese Medicine, 24 Heping Road, Harbin, Heilongjiang, People’s Republic of China, Email zyylq78@126.comAbstract: Anxiety disorders are highly prevalent psychiatric conditions that impair quality of life and daily functioning. Despite the availability of pharmacological and psychotherapeutic treatments, limitations such as suboptimal efficacy, adverse effects, and high relapse rates remain unresolved. Traditional Chinese Medicine (TCM) has emerged as a complementary approach, yet its theoretical complexity and lack of standardized evidence hinder broader clinical integration. This review provides a comprehensive synthesis of the role of TCM in the management of anxiety disorders, covering classical theories, epidemiological features, diagnostic principles, therapeutic strategies, and modern innovations. It outlines the pathogenesis of anxiety from a TCM perspective, including syndrome types such as liver Qi stagnation and heart-spleen deficiency, and discusses personalized treatment modalities such as herbal prescriptions, acupuncture, and five-element music therapy. Importantly, it highlights advances in TCM standardization through data mining, integration with metabolomics and neuroimaging, and emerging tools for objective evaluation, such as fNIRS. Clinical trials suggest that TCM interventions may achieve comparable or superior symptom control with fewer adverse effects than conventional treatments. This review offers a structured reference for clinicians and researchers aiming to understand the evolving role of TCM in anxiety management and its potential contribution to future integrative care models.Keywords: anxiety disorder, DSM-5, ICD-11, 5-HT, TCM